OPTIMALISASI PRODUKSI OLAHAN BEKU DARI IKAN DAN UDANG PADA UD. KAYA RASA DI KELURAHAN SUNGAI KELEDANG KECAMATAN SAMARINDA SEBERANG - Ria Puspita Sari; Gusti Haqiqiansyah; Said Abdusysyahid (2339-1324, 2020)
The study aims to find out the frozen production has reached optimal conditions. The method used in this research is the case study method with the required data are primary data and secondary data. Primary data obtained by direct interview with respondents. Secondary data needed includes data from the Samarinda City Fisheries and Maritime Agency in numbers. The data is then processed with the a computer using the LINDO 6.1 program. The results of this study shows that UD. Kaya Rasa is not reaching an optimal condition yet. This is shown by a difference between actual profit and optimalization result profit as Rp. 675.000,00.